Operations strategies of a selected Fair Price Shop Awards 2004-2005 winners - Islam, Rafikul; Salleh, Zasali (Kulliyyah of Economics and Management Sciences, IIUM, 2008)

(untitled)
The term fair price is commonly used in retail business. To encourage retail business outlets to keep fair prices for their products, Malaysian Government has instituted Fair Price Shop Awards since 2003. More than 100 retail outlets win this award every year in 14 categories. The present paper attempts to identify the most common strategies that have been used by a selected winning companies in 2004-2005 to sell their products at fair price, which help them in maintaining profit, staying competitive in the marketplace, and attaining customer satisfaction. For data collection, we conducted face to face interviews with the operations managers of these companies. It is expected that the findings will provide guidelines to similar companies to stay competitive in the marketplace.